Decentralized Revenue Management and Health Service Delivery in Local Governments in Uganda: A Case Study of Kabale District Local Government - Christine, Nayebare (Kabale University, 2022)
A Dissertation Submitted to the Directorate of Postgraduate Training in Partial Fulfilment of the Requirements for the Award of a Master’s Degree in Public Administration and Management of Kabale University